THE BASIS OF TERMINATION OF THE EMPLOYMENT CONTRACT IN THE LEGISLATION OF THE REPUBLIC OF UZBEKISTAN (Conferencea, 2021)
It is known that the role of labour in the history of human development cannot be overemphasized. Because, the formation of the material basis of any society depends on the work of members of that society. The provision of the constitutional right of citizens to work is guaranteed not only by the conclusion or amendment of the employment contract, but also by the legal regulation of the procedure for the termination of the employment contract in the legislation in a clear and complete way, as well as by the employment activity on this basis